Limits of the Obligation to Seek Knowledge and Teach It and Stages in Islamic Education (Gender Studies Perspective) - Emha Dzia'ul Haq (Yayasan Zia Salsabila, 2023)
This article aims to determine the limits of a person's obligations in seeking knowledge and teaching it as well as the stages in an Islamic perspective. Qualitative research was chosen in this paper to reveal data using data collection techniques from several sources. Based on these results, it was found that there are no limits to the pursuit of knowledge, which has been explained in the hadith of the Prophet, which means